The neurological wake-up test in severe pediatric traumatic brain injury: a long term, single-center experience - Mulder, Hilde D.; Helfferich, Jelte; Kneyber, Martin C. J. (Frontiers in Pediatrics, 2024)
Objectives: To describe the use and outcomes of the neurological wake-up test (NWT) in pediatric severe traumatic brain injury (pTBI).Design: Retrospective single-center observational cohort study.Setting: Medical-surgical tertiary pediatric intensive care unit (PICU) in a university medical center and Level 1 Trauma Center.Patients: Children younger than 18 years with severe TBI (i.e., Glasgow Coma Scale [GCS] of ≤ 8) admitted between January 2010 and December 2020. Subjects with non-traumatic brain injury were excluded.Of 168 TBI patients admitted, 36 (21%) met the inclusion criteria. Median age was 8.5 years [2 months-16 years], 5 patients were younger than 6 months. Median initial Glasgow Coma Scale (GCS) and Glasgow Motor Scale (GMS) was 6 [3-8] and 3 [1-5]. NWTs were initiated in 14 (39%) patients, with 7 (50%) labelled as successful. Fall from a height was the underlying injury mechanism in those seven. NWTfailure occurred in patients admitted after traffic accidents. Sedation use in both NWTsubgroups (successful vs failure) was comparable. Cause of NWT-failure was non-arousal (71%) or severe agitation (29%). Subjects with NWT failure subsequently had radiological examination (29%), repeat NWT (43%), continuous interruption of sedation (14%) or intracranial pressure (ICP) monitoring (14%). The primary reason for not doing NWTs was intracranial hypertension in 59%. Compared to the NWT-group, the non-NWT group had a higher PRISM III score (18.9 versus 10.6), lower GCS/GMS at discharge, more associated trauma, and circulatory support. Nine patients (25%) died during their PICU admission, none of them had an NWT.We observed limited use of NWTs in pediatric severe TBI. Patients who failed the NWT were indistinguishable from those without NWT. Both groups were more severely affected compared to the NWT successes. Therefore, our results may indicate that only a select group of severe pTBI patients qualify for the NWT.